Decision-making in organizations under uncertainty based on cognitive model: The NU experience. - Mgbere, Chinwi (Nazarbayev University Graduate School of Business, 2016)
Professional experience shows top, middle and low-level management must be ready to make decision at their respective levels instead of demonstrating an attitude of avoidance, falling into a reactive mode and losing holistic understanding of the bigger picture. This leads to information and decision-making going up and down the hierarchical ladder resulting in critical loss in duration. It is imperative that sustainable strategy receives paramount attention considering the constraints in financial and human resources, uncertainty and complexity in an organisations' environment. Sustainable decision making is achievable through interaction and influence between decision makers (stakeholders) during project implementation. Projects stand to benefit from this interaction through exchange of knowledge and motivators, given that a competent project manager with high cognitive potential is involved. The goal of this thesis is to develop a decision-making model where decision making leaders create conditions that allow teams to manage themselves effectively and enhance team performance at their best.
Thesis
Keywords: decision-making; attitude; organization